Rozwijanie osobowości dziecka w ramach aktywności twórczej = Personality development of the child in the creative activity - Famuła-Jurczak, Anita (Zielona Góra ; Skarbona: Stowarzyszenie Polskich Muzyków Kameralistów)
The natural form of activity of the unit is taken by her activity. The unit recognizes the reality that surrounds her through all forms of activities that allow you not only to the knowledge of the world but also to Express themselves and build self-image.
Keywords: aktywność; aktywność artystyczna; aktywność twórcza; osobowość; wychowawca; wychowanie; activity; artistic activity; personality; education; educator